Impact of food behavior on children’s health. A case study - Talaghir, Laurentiu Gabriel; Barna, Octavian; Serea, Cristian; Barna, Iuliana Petronela; Banu, Elena Ariela (Progress in Nutrition, 2020)
The current study evaluated the impact of food behavior on the incidence of gastrointestinal disorders, food allergies, and overweight, on children. For this purpose, a series of questionnaires regarding diet, eating habits, and the incidence of childhood affections, were completed by the parents of 212 children aged between 0 and 14 years, patients in the St. John Children’s Hospital of Galati, Romania. Eating patterns were investigated, including the frequency of eating breakfast, fruits and vegetable intake, fast food, and carbonated drinks consumption. The results showed an increase in the incidence of digestive disorders, by 6.13% for boys and by 4.72% for girls, especially for those who eat daily fast food compared to children who consumed fast food only two to three times a week and respectfully, an increase in the incidence of food allergies by 8.96% for boys and 6.60% for girls in case of daily consumption of carbonated drinks compared to children who consumed this type of beverages only once a week or less. In the case of overweight children, the results also displayed a low-frequency consumption of fresh fruits and vegetables, by 5.19% for boys and 4.71% for girls, less than two times a week, compared with the daily consumption of these products.